TI_GERICHTE 32.2009.134 vom 28. Mai 2009 , Perizia del SAM: nessun diritto a una riformazione professionale e a una rendita - TI Tribunale d'appello (2009)
Perizia del SAM: nessun diritto a una riformazione professionale e a una rendita